Efficacy and safety of nerinetide for the treatment of acute ischaemic stroke (ESCAPE-NA1): a multicentre, double-blind, randomised controlled trial. Issue 10227 (14th March 2020) - Hill, Michael D; Goyal, Mayank; Menon, Bijoy K; Nogueira, Raul G; McTaggart, Ryan A; Demchuk, Andrew M; Poppe, Alexandre Y; Buck, Brian H; Field, Thalia S; Dowlatshahi, Dar; van Adel, Brian A; Swartz, Richard H; et al.
Summary: Background: Nerinetide, an eicosapeptide that interferes with post-synaptic density protein 95, is a neuroprotectant that is effective in preclinical stroke models of ischaemia-reperfusion. In this trial, we assessed the efficacy and safety of nerinetide in human ischaemia-reperfusion that occurs with rapid endovascular thrombectomy in patients who had an acute ischaemic stroke. Methods: For this multicentre, double-blind, randomised, placebo-controlled study done in 48 acute care hospitals in eight countries, we enrolled patients with acute ischaemic stroke due to large vessel occlusion within a 12 h treatment window. Eligible patients were aged 18 years or older with a disabling ischaemic stroke at the time of randomisation, had been functioning independently in the community before the stroke, had an Alberta Stroke Program Early CT Score (ASPECTS) greater than 4, and vascular imaging showing moderate-to-good collateral filling, as determined by multiphase CT angiography. Patients were randomly assigned (1:1) to receive intravenous nerinetide in a single dose of 2·6 mg/kg, up to a maximum dose of 270 mg, on the basis of estimated or actual weight (if known) or saline placebo by use of a real-time, dynamic, internet-based, stratified randomised minimisation procedure. Patients were stratified by intravenous alteplase treatment and declared endovascular device choice. All trial personnel and patients were masked to sequence and treatment allocation. All patients underwent endovascular thrombectomy and received alteplase in usual care when indicated. The primary outcome was a favourable functional outcome 90 days after randomisation, defined as a modified Rankin Scale (mRS) score of 0–2. Secondary outcomes were measures of neurological disability, functional independence in activities of daily living, excellent functional outcome (mRS 0–1), and mortality. The analysis was done in the intention-to-treat population and adjusted for age, sex, baseline National Institutes of Health Stroke Scale score, ASPECTS, occlusion location, site, alteplase use, and declared first device. The safety population included all patients who received any amount of study drug. This trial is registered with ClinicalTrials.gov, NCT02930018 . Findings: Between March 1, 2017, and Aug 12, 2019, 1105 patients were randomly assigned to receive nerinetide (n=549) or placebo (n=556). 337 (61·4%) of 549 patients with nerinetide and 329 (59·2%) of 556 with placebo achieved an mRS score of 0–2 at 90 days (adjusted risk ratio 1·04, 95% CI 0·96–1·14; p=0·35). Secondary outcomes were similar between groups. We observed evidence of treatment effect modification resulting in inhibition of treatment effect in patients receiving alteplase. Serious adverse events occurred equally between groups. Interpretation: Nerinetide did not improve the proportion of patients achieving good clinical outcomes after endovascular thrombectomy compared with patients receiving placebo. Funding: Canadian Institutes for Health Research, Alberta Innovates, and NoNO.